Influence of CNF Encodings of AtMost-1 Constraints on UNSAT-based PMSAT Solvers - Menai, M. El B.; Al-Yahya, T.N. (Informatica)
Influence of CNF Encodings of AtMost-1 Constraints on UNSAT-based PMSAT Solvers